Penerapan dan Pembaharuan Hukum Islam Dalam Tata Hukum Mesir dan Turki - Rif'at Husnul Ma'afi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2010)
This article explains the application of islamic law and its reformation in Egypt and Turkey. The two countries have similarities in their experience of the effort of reforming islamic law. Both have a long history in experiencing the appearance of the four islamic schools of law with the prevalence of the Hanafy school in the masses. When the Ottoman empire ruled Egypt, the ottoman law was also applied in Egypt which in turn also contributed the later development of Egyptian legal system. In addition, there was close encounter between Islam and the West since the 19th Century, which enabled muslims to learn from the West and eventually took the form of secularization in Turkey and Egypt. Nonetheless, in its develepomnet, Egypt is more influenced by islamic jurisprudence basauece of the prevalence of islamic schools of law in Egypt. In contrast, Turkey’s legal system was more secularized especially during and after the reign of Kemal Attaturk.